Performance evaluation of different modulation techniques in optical OFDM - Rahman, Muhammad Towfiqur (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
In the recent years, there have been extensively studied on optical OFDM (O-OFDM) transmission technology. It is considered as a promising technology for future ultra-high-speed optical transmission. Nonlinearity of the modulator, energy efficienciency and utilization of the bandwidth are the major challenges for optical OFDM. This research has modified the CO-OFDM system using OptiSystem such as optical amplifiers, upconverter, polarizer splitters and combiners. Furthermore, the OptiSystem software is used to reconfigure and simulate to achieve the research objectives. The performances of energy and bandwidth efficiencies of a radio-over-fiber (RoF) system utilizing M-QAM (quadrature amplitude modulation), OOK (On-Off-keying) and M-PAM (Pulse amplitude modulation) are considered in this research. The RoF system utilizes single channel CO-OFDM system with 10 GHz spacing has been reconfigured using five different modulation schemes at both short and long fiber lengths. Simulation results using OptiSystem shows that, OOK achieves the best results among other modulation schemes in the short distance as less than 100 km. Meanwhile, 128-QAM out performs other modulation schemes for long distance transmission (1000 km). It also utilized the maximum bandwidth. The results show that the modulation schemes are able to improve both the BER and the power efficiencies. An improvement of M-QAM BER performance was done when the amplifier power was increased. But, this was achieved when there was a trade off between the noise and signal quality. For example, better BER 10-13 was achieved for M-QAM, with the higher OSNR for the baseband noise channel. In addition, M-PAM and OOK modulation schemes had achieved minimum BER of 10-10. Finally, these results are compared with other earlier work using the same modulation schemes for benchmarking.